The Relationship between pH and Heavy Metal Ion Sorption by Algal Biomass - Ying-Zhong Tang; Karina Y.H. Gin; M.A. Aziz (Adsorption Science & Technology)
The relationship between pH and heavy metal ion sorption by the biomass of two algal species was studied under controlled experimental conditions. It was observed that increasing heavy metal ion sorption by algal biomass with pH mainly arose from a change in algal cell properties, provided that the pH was below the level where the heavy metal ions started to precipitate. A drastic increase in metal ion sorption capacity (‘inflection point’) was observed at pH 4.5 for the algal biomass used in the study. All the experimental observations on the mutual effects between pH and metal sorption for four heavy metal ions (Cd 2+ , Cu 2+ , Pb 2+ and Zn 2+ ) and two algal species suggested that the mutual effects between pH and heavy metal ion sorption can be explained in terms of ion exchange and coulombic attraction between the heavy metal ions and the algal biomass. A ‘positive feedback’ was also suggested for the mutual effects between pH and heavy metal ion removal at higher initial pH levels, where the sorption of heavy metal ions may enhance their hydrolysis.